ANALISIS KEBERADAAN RHODAMIN B PADA IKAN CAKALANG FUFU YANG BEREDAR DI PASARAN KOTA MANADO - Dianti, Ni Wayan; Fatimawali, Fatimawali; Yudistira, Adithya (PHARMACON, 2012)
Rhodamin B is a synthetic dye that was banned for use in foods and is certified as a hazardousmaterial according to Minister of Health of Indonesian Republic No. 722/Menkes/Per/IX/1988because it can cause liver, kidney, and spleen damage, and followed by anatomical changes in theform of organ enlargement. Rhodamin B dye is often used for a food and beverage products. Thestudy was conducted to identify Rhodamin B on cakalang fufu in the market of Manado city.Cakalang fufu samples were taken from four markets in the city of Manado, namely : the Paal 2market, Bahu market, Karombasan market and Bersehati 45 Market. Samples were extracted by twomethods, the method of extraction followed by purification and extraction method using wool yarnand absorption followed by identification using thin layer chromatography (TLC) and detected withUV light 254 nm and 366 nm. Rhodamin B content is read using a UV-Vis spectrophotometry. Theresult showed that out of eight samples examined with two tests, there are four samples containingRhodamin B with higher levels of the average value of Rhodamin B in samples, that is from themerchant two of Bahu Market is 0,054 ug/ml, at merchant two Karombasan market is 0.184 ug/ml,34merchant one at Bersehati 45 Market is 0.103 ug/ml and merchant two at Bersehati 45 is 0.514 ug/ml.Based on these results, some of cakalang fufu circulating in Manado City Markets are not safe forconsumption.Keywords: Rhodamin B, Cakalang fufu, TLC and UV-Vis spectrophotometry